2017
DOI: 10.1126/scitranslmed.aan4669
|View full text |Cite
|
Sign up to set email alerts
|

A degradation fragment of type X collagen is a real-time marker for bone growth velocity

Abstract: Despite its importance as a key parameter of child health and development, growth velocity is difficult to determine in real timebecause skeletal growth is slowand clinical tools to accurately detect very small increments of growth do not exist. We report discovery of a marker for skeletal growth in infants and children. The intact trimeric noncollagenous 1 (NC1) domain of type X collagen, the markerwe designated as CXMfor Collagen X Marker, is a degradation by-product of endochondral ossification that is rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 40 publications
2
71
0
1
Order By: Relevance
“…Most interestingly, a recently published study has shown that a group of fragments containing the entire C1q domain and variable portions of the attached linker and collagenous region designated as CXM, was a degradation product of type X collagen during endochondral ossification and an ideal biomarker for the overall growth plate activity 32 . The serum-based assay for CXM used in this study was built upon a mAb X34 specifically targeting a multimeric form of the NC1 domain, the~50 kDa NC1 region 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, a recently published study has shown that a group of fragments containing the entire C1q domain and variable portions of the attached linker and collagenous region designated as CXM, was a degradation product of type X collagen during endochondral ossification and an ideal biomarker for the overall growth plate activity 32 . The serum-based assay for CXM used in this study was built upon a mAb X34 specifically targeting a multimeric form of the NC1 domain, the~50 kDa NC1 region 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the association between asymptomatic viral infections and growth . To better assess the growth impact of non‐chronic viral infections, one should thus probably use with a short follow‐up period a more sensitive outcome variable, such as knemometry, plasma concentrations of insulin‐like growth factor or collagen X .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COLX involved in hematopoiesis, mineralization, and endochondral ossification. The COLX is stored in the hypertrophic zone and is removed during the endochondral ossification process (Chang et al 2012;Gu et al 2014;Coghlan et al 2017). Type X-collagen production increases progressively during the development of the embryonic framework, thereby accelerating embryo growth (Prickett 2014).…”
Section: Resultsmentioning
confidence: 99%